2013
DOI: 10.1063/1.4821133
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength sensitive AlGaN/GaN metal-insulator-semiconductor-insulator-metal ultraviolet sensor with balanced ultraviolet/visible rejection ratios

Abstract: We proposed and fabricated a metal-insulator-semiconductor-insulator-metal type dual-wavelength sensitive UV sensor by using an AlGaN/GaN hetero-structure layer epitaxially grown on a sapphire substrate and a thin Al2O3 layer inserted between AlGaN and Ni Schottky electrodes to reduce dark current and improve the UV/visible rejection ratio. The proposed sensor shows high photo-responsive current to both UV wavelength regimes with a significantly improved UV/visible rejection ratio under the regime of the GaN-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Exposure to UV-A and UV-B radiations can lead to skin aging, pigmentation, skin cancer, cataracts, and other ailments, and hence there is a high demand for UV monitoring sensors. Various UV-sensitive materials and detectors have been reported in the last decade, which include silicon photodetectors , and photoconductive devices and sensors based on ZnO nanostructures, GaN, Ga 2 O 3 , and others. Zhang et al synthesized high-quality β-Ga 2 O 3 film using the modified metal–organic chemical vapor deposition method and fabricated β-Ga 2 O 3 film-based photodetectors, showing high photoresponsivity and fast response speed . Hossein-Babaei et al reported a Schottky-type UV sensor, including Ag–TiO 2 –Ti structure, exhibiting fast response and recovery time, consuming less than 10 pW of electric power .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to UV-A and UV-B radiations can lead to skin aging, pigmentation, skin cancer, cataracts, and other ailments, and hence there is a high demand for UV monitoring sensors. Various UV-sensitive materials and detectors have been reported in the last decade, which include silicon photodetectors , and photoconductive devices and sensors based on ZnO nanostructures, GaN, Ga 2 O 3 , and others. Zhang et al synthesized high-quality β-Ga 2 O 3 film using the modified metal–organic chemical vapor deposition method and fabricated β-Ga 2 O 3 film-based photodetectors, showing high photoresponsivity and fast response speed . Hossein-Babaei et al reported a Schottky-type UV sensor, including Ag–TiO 2 –Ti structure, exhibiting fast response and recovery time, consuming less than 10 pW of electric power .…”
Section: Introductionmentioning
confidence: 99%
“…UV monitoring sensors utilize the change in conductivity by adsorption/desorption between oxygen molecules and the holes of semiconductor ZnO [117][118][119], gallium nitride (GaN) [120,121], titanium dioxide (TiO 2 ) [122], and CNT [123]. Zhang et al fabricated the Kevlar fiber coated with ZnO nanowires by plasma etching, which directly responded to UV exposure from 0.2 to 1 mW cm −2 [124].…”
Section: Photo-sensing Fibersmentioning
confidence: 99%
“…Nitride materials are attractive candidates for various optical applications due to their wide direct bandgaps and highly crystalline qualities following epitaxial growth [ 1 , 2 , 3 ]. In particular, nitride-based semiconductors have been broadly used in important applications such as high-power/high-speed electron devices, visible/UV laser diodes, LEDs, and UV sensors [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%